Modal Superlatives And 3-Place Vs. 2-Place -Est - Maribel Romero (Baltic International Yearbook of Cognition, Logic and Communication, 2010)
Superlative sentences with modal modifiers like possible give rise to the so-called 'modal superlative reading' (Larson 2000, Schwarz 2005). The present paper uses this reading to investigate an open issue in degree constructions: whereas two different lexical entries have been argued to exist for the comparative morpheme -er (3-place and 2-place), it is not clear whether two entries are needed for the superlative morpheme -est. The paper argues that, with 3-place –est, otherwise unmotivated syntactic material would to have to be postulated and that, even with this material, not all modal superlative examples would be assigned correct truth conditions. In contrast, 2-place -est can generate the modal superlative reading in all the cases, as shown in Romero (to appear, under review). Modal superlative sentences, thus, provide evidence that 2-place –est is needed in the grammar.